Histoire, mémoire et tribus ou les aarch de 2001 en Kabylie - Nassim Amrouche (Conserveries Mémorielles)
The riots that have bloodstained Kabylie in the spring of 2001 have raised different problematics. Beyond the human drama which has resulted in more than a hundred deaths and a thousand wounded, this contestation formulated itself around an anachronic organization: the aarch. Ancient sociopolitical system for which the last traces of existence date back to the end of the XIXe century, it has mobilized (by) the tribe reconfigured according to cotemporaneous needs. This use of a Maghrebian social organization has allowed an inscription through time by the memory mobilized by the tribe.Indeed, in a political perspective, the aarch, to contest the present, have underlined historical and memorial heritages erased par the Algerian nation state. Mobilizing the history of the war of decolonization that founded the independence of the State, the aarch directly attacked the vouloir vivre ensemble, redefining the constitutive basis of the nation. This memorial and historical dynamic has also allowed the militants and partisans to revisit a remoter past: crisis in the nationalist movement, post Independence social movements, etc. This revision of memories for which culture and language remain the base, has allowed to envisage cultural and identity territory that goes beyond the frontiers of the nation state.If these data are those of the politics, the militants, the social basis of the movement, which has mobilized up to a 1,5 million of people, have re-use these tools of contestation in order to transform them into sources of the contemporaneous socioeconomic malaise.